Analisis Penerapan PSAK 241 Pada Usaha Budidaya Bibit Ikan Bandeng UD Matsya Ajeg - Ni Putu Widiastiti; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2026)
This study aims to analyze the application of biological asset accounting in the milkfish (Chanos chanos) fry farming business of UD Matsya Ajeg based on PSAK 241 on Agriculture. The study is motivated by the fact that many aquaculture businesses have not yet implemented biological asset accounting standards, resulting in financial reports that are inadequate for supporting business decision-making. The research employed a qualitative descriptive approach, with primary data obtained through observations and interviews with the business owner, and secondary data derived from financial records. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results indicate that UD Matsya Ajeg has not formally recognized biological assets; fish eggs are still recorded as inventory and not classified as biological assets. In measurement, the company uses historical cost, whereas PSAK 241 stipulates fair value less estimated selling costs. Moreover, the presentation and disclosure of biological assets in financial statements remain simple and unsystematic. Full implementation of PSAK 241 is necessary to enhance the relevance, reliability, and transparency of financial information, thereby supporting effective managerial decision-making